(untitled) (Law and world, 2016)
Using a comparative legal study and based on the samples of Germany, The UK and EU system of corporate governance, this article reviews the importance of soft law in the field of corporative governance. The main problem, solving of which is tried by respective European regulation, is a real and proper operation of soft law in corporate governance codes. This appears to be the basis of the recommendations made by the European Commission regarding the quality of corporate governance reporting. The part of the document focuses on the growth of the principle“comply or explain,“ under which the companies share either corporate governance requirements under respective codes or properly substantiate reasons of not sharing it. This information is published in the annual corporate governance reports. Publication of such reports is obligatory for large corporations in Germany and The UK.